2018
DOI: 10.1158/2159-8290.cd-17-0699
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo E2F Reporting Reveals Efficacious Schedules of MEK1/2–CDK4/6 Targeting and mTOR–S6 Resistance Mechanisms

Abstract: Targeting cyclin-dependent kinases 4/6 (CDK4/6) represents a therapeutic option in combination with BRAF inhibitor and/or MEK inhibitor (MEKi) in melanoma; however, continuous dosing elicits toxicities in patients. Using quantitative and temporal reporting, we show that continuous MEKi with intermittent CDK4/6 inhibitor (CDK4/6i) led to more complete tumor responses versus other combination schedules. Nevertheless, some tumors acquired resistance that was associated with enhanced phosphorylation of ribosomal S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 34 publications
6
63
1
Order By: Relevance
“…S1G and S1H) and an increase in CCND1 ( Supplementary Fig. S1H) total protein levels, both of which are consistent with previous studies (7,11). Palbociclib inhibition did not alter the MAPK signaling components RAF and MEK, however we did observe an increase in phospho-ERK levels (Fig.…”
Section: Nras-dependent Melanoma Cell Lines Are Sensitive To Pharmacosupporting
confidence: 91%
See 1 more Smart Citation
“…S1G and S1H) and an increase in CCND1 ( Supplementary Fig. S1H) total protein levels, both of which are consistent with previous studies (7,11). Palbociclib inhibition did not alter the MAPK signaling components RAF and MEK, however we did observe an increase in phospho-ERK levels (Fig.…”
Section: Nras-dependent Melanoma Cell Lines Are Sensitive To Pharmacosupporting
confidence: 91%
“…4H). These data suggest that reengagement of mTOR signaling is associated with resistance to trametinib and palbociclib treatment in NRAS mutant melanoma, which is consistent with known in vivo and clinical mechanisms of inhibitor resistance (7,11).…”
Section: Egfr-pi3k-akt Signaling Modulates Resistance To Trametinib/supporting
confidence: 81%
“…While no changes in mTOR signalling components have been documented in long-term resistance models, CDK4/6 inhibitor-resistant cell lines have demonstrated sensitivity to mTORC1/2 inhibition (Michaloglou et al 2018). Other signalling changes include NRAS amplification or mutation in an NRAS model of melanoma co-treated with MEK1 inhibition and CDK4/6 inhibition (Teh et al 2018), and alterations in FGF/FGFR signalling in resistance to CDK4/6 inhibitors both alone and in combination with endocrine therapy (Cruz et al 2018, Mao et al 2018, Shee et al 2018. Finally, an activating mutation in PIK3CA E545K , was shown to display a resistance phenotype to combination MEK and CDK4/6 inhibitors, and the outgrowth of a clone expressing this mutation caused recurrence in a melanoma patient treated with these inhibitors (Romano et al 2018).…”
Section: Growth Factor Signalling Pathwaysmentioning
confidence: 99%
“…Phospho‐S6 is a reliable surrogate biomarker/readout of mTOR axis activation and has been investigated in numerous studies focusing on neoplastic and non‐neoplastic conditions . In a recent study, phospho‐S6 was shown to be at least partially responsible for resistance to combinational mitogen‐activated protein kinase MEKi therapy with CDK4/6 inhibitors in melanoma . To date, there are no studies investigating mTOR pathway activation in hair follicle tumors through protein expression on formalin fixed tissue.…”
Section: Introductionmentioning
confidence: 99%